Seroprevalence of Strongyloides stercoralis infection in a South Indian adult population. - Saravanan Munisankar; Anuradha Rajamanickam; Suganthi Balasubramanian; Satishwaran Muthusamy; Chandra Kumar Dolla; Pradeep Aravindan Menon; Ponnuraja Chinnayan; Christopher Whalen; Paschaline Gumne; Inderdeep Kaur; Varma Nadimpalli; Akshay Deverakonda; et al. (PLoS Neglected Tropical Diseases, 2022)
Background The prevalence of Strongyloides stercoralis infection is estimated to be 30-100 million worldwide, although this an underestimate. Most cases remain undiagnosed due to the asymptomatic nature of the infection. We wanted to estimate the seroprevalence of S. stercoralis infection in a South Indian adult population. Methods To this end, we performed community-based screening of 2351 individuals (aged 18-65) in Kanchipuram District of Tamil Nadu between 2013 and 2020. Serological testing for S. stercoralis was performed using the NIE ELISA. Results Our data shows a seroprevalence of 33% (768/2351) for S. stercoralis infection which had a higher prevalence among males 36% (386/1069) than among females 29.8% (382/1282). Adults aged ≥55 (aOR = 1.65, 95% CI: 1.25-2.18) showed higher adjusted odds of association compared with other age groups. Eosinophil levels (39%) (aOR = 1.43, 95% CI: 1.19-1.74) and hemoglobin levels (24%) (aOR = 1.25, 95% CI: 1.11-1.53) were significantly associated with S. stercoralis infection. In contrast, low BMI (aOR = 1.15, 95% CI: 0.82-1.61) or the presence of diabetes mellitus (OR = 1.18, 95% CI: 0.83-1.69) was not associated with S. stercoralis seropositivity. Conclusions Our study provides evidence for a very high baseline prevalence of S. stercoralis infection in South Indian communities and this information could provide realistic and concrete planning of control measures.